Mechanical properties and performance of engineering ceramics and composites VII - A Collection of papers presented at the 36th international conference on Advanced ceramics and composites Januari 22-27, (2012 : Daytona Beach, Florida); Singh, Dileep; Salem, J. A. (Jonathan A.), 1960-; Halbig, Michael; Mathur, Sanjay (New York : John Wiley, 2012)
Includes bibliographical references and author index